Serviço social e luta antirracista: contribuição das entidades da categoria no combate ao racismo - Moreira, Tales Willyan Fornazier (2019)
This work focused on studying of the ethnic-racial debate within the Brazilian Social Service, based on the entities’ analysis of the professional category (ABEPSS, CFESS and ENESSO) in the 2017-2018 period, considering the need to progress further in this discussion within the profession. Thus, the purpose of this research was to identify the contribution of these entities in the construction of mediations that will strengthen the anti-racist struggle, considering the emancipatory social direction expressed in the professional Ethical-Political Project. Interviews were conducted with one representative from each of the three entities, as well as with the promulgate agent of the race debate in the GTP “Social Work, Exploitation / Gender Oppression Relations, Race / Ethnicity, Generation, Sexualities” for 2017- 2018. It was an intentional choice of the participants, whose criterion used was the fact that they are black women in this space of protagonism of the entities and the notorious involvement and commitment to the anti-racist struggle inside and outside the profession. The research had as elementary hypothesis the fact that the entities of the category have a strategic and central role for the intensification of the ethnic-racial discussion and, consequently, of the hegemonic socio-political direction of Social Service itself. The results of the research showed the internal obstacles, limits and contradictions that prevent the anti-racist struggle from being more strongly incorporated by the profession. However, they also show that the category is on an upward trend in relation to the recognition of the importance and centrality of the ethno-racial issue and that the entities have been contributing significantly to this advance, within the framework of the Ethical-Political Project of Social Service